1999
DOI: 10.1083/jcb.147.4.831
|View full text |Cite
|
Sign up to set email alerts
|

A Role for P21-Activated Kinase in Endothelial Cell Migration

Abstract: The serine/threonine p21-activated kinase (PAK) is an effector for Rac and Cdc42, but its role in regulating cytoskeletal organization has been controversial. To address this issue, we investigated the role of PAK in migration of microvascular endothelial cells. We found that a dominant negative (DN) mutant of PAK significantly inhibited cell migration and in-creased stress fibers and focal adhesions. The DN effect mapped to the most NH2-terminal proline-rich SH3-binding sequence. Observation of a green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
253
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(282 citation statements)
references
References 48 publications
26
253
2
1
Order By: Relevance
“…In agreement with our data, Kiosses et al (1999) demonstrated that the amino-terminal proline-rich domain of Pak, and not the Rac/Cdc42 interaction domain, was required for the inhibition of cell migration by a dominant negative Pak protein.…”
Section: Rho Gtpases and Effectors In Hgf Biologysupporting
confidence: 80%
“…In agreement with our data, Kiosses et al (1999) demonstrated that the amino-terminal proline-rich domain of Pak, and not the Rac/Cdc42 interaction domain, was required for the inhibition of cell migration by a dominant negative Pak protein.…”
Section: Rho Gtpases and Effectors In Hgf Biologysupporting
confidence: 80%
“…Experimental observations further increase the relevance of such questions: Fashena et al (2002) showed that keratocyte-like movements occur in MCF7 breast adenocarcinoma cells overexpressing HEF1 (a cas-family protein), with the formation of a large leading lamellipod, enhanced ruffling and pronounced trailing edge. Similar observations were made in human microvascular endothelial cell line, HMEC-1 (Kiosses et al, 1999;Fischer et al, 2003). More surprisingly, Asano et al (2004) reported that the deletion of a single gene, amiB, from Dictyostelium cells, transforms this typically amoeboid cell to a crescent-shaped keratocyte-like cell with persistent movement and higher velocity.…”
Section: Robustnesssupporting
confidence: 67%
“…These defects could be explained by an alteration of Vav-2-Rac-1-PAK signaling. In endothelial cells, PAK activity is necessary for migration, and it is up-regulated by the formation of new adhesions; in accordance with this, overexpression of a PAK dominant negative form inhibits cell migration (45). However, transfection of a constitutively active PAK mutant was also detrimental for migration because PAK inactivation is required for detachment and tail retraction.…”
Section: Discussionmentioning
confidence: 65%